2010
DOI: 10.33899/rden.2010.9016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling an Irrigation Solution During Preparation of Implant Site on Heat Generation Using Elite System for implant.(Experimental Study)

Abstract: ‫الخالصة‬ ‫األهداف‬ : ‫ارة‬ ‫حر‬ ‫درجة‬ ‫غند‬ ‫الغسل‬ ‫ئل‬ ‫سا‬ ‫تخدام‬ ‫اس‬ ‫غند‬ ‫املتودلة‬ ‫ارة‬ ‫احلر‬ ‫هة‬ ‫مللار‬ 5 ‫و‬ ‫ية‬ ‫مئو‬ 25 ‫الزراػة‬ ‫هظام‬ ‫ات‬ ‫أدو‬ ‫تخدام‬ ‫ابس‬ ‫الزرػة‬ ‫موكع‬ ‫حتضري‬ ‫خالل‬ ‫ية‬ ‫مئو‬ Elite . ‫املواد‬ ‫يلة‬ ‫والطر‬ : ‫ماء‬ ‫خض‬ ‫مؼدل‬ ‫إن‬ ‫ػلام‬ ‫امليلنم‬ ‫هجاز‬ ‫ػىل‬ ‫ألبلري‬ ‫الفخذ‬ ‫غظم‬ ‫تخدام‬ ‫ابس‬ ‫وذكل‬ ‫الؼظم‬ ‫يف‬ ‫احلفر‬ ‫معلية‬ ‫خالل‬ ‫املتودلة‬ ‫ارة‬ ‫احلر‬ ‫درجة‬ ‫للياس‬ ‫اري‬ ‫احلر‬ ‫املزدوج‬ ‫تخدام‬ ‫اس‬ ‫مت‬ ‫اثبت‬ ‫الغسل‬ . ‫غند‬ ‫ثثبيهتا‬ ‫مت‬ ‫الغسل‬… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It eliminates heated bone chips from the osteotomy and reduces friction during drilling, thus contributing to decreased generation of the frictional heat 13 . Saline at room temperature can provide sufficient cooling during conventional drilling, although in dense cortical bone or at high rotational speed deleterious bone temperatures might be generated 14 . Cooled saline is proved to be more effective when drilling without the surgical guide 15 .…”
Section: Introductionmentioning
confidence: 99%
“…It eliminates heated bone chips from the osteotomy and reduces friction during drilling, thus contributing to decreased generation of the frictional heat 13 . Saline at room temperature can provide sufficient cooling during conventional drilling, although in dense cortical bone or at high rotational speed deleterious bone temperatures might be generated 14 . Cooled saline is proved to be more effective when drilling without the surgical guide 15 .…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that while there are several parameters that increase bone temperature during drilling, cooling (as external irrigation in their case) can be the only and the most important factor in limiting this increase in bone temperature and must be used for bone drilling. On the other hand, Shakouri et al [3], Sener et al [17], Al-Dabag and Sultan [23], and Sindel et al [24] determined the efficiency of external cooling with normal saline as coolant. They also indicated similar positive influence in limiting the maximum temperature elevation.…”
Section: Discussionmentioning
confidence: 99%